2020
DOI: 10.3390/cells9071722
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Extracellular Vesicles Released by the Pathogenic Yeast-Like Fungi Candida glabrata, Candida parapsilosis and Candida tropicalis

Abstract: Candida spp. yeast-like fungi are opportunistic pathogens in humans and have been recently found to release extracellular vesicles (EVs) that are involved in many vital biological processes in fungal cells. These include communication between microorganisms and host–pathogen interactions during infection. The production of EVs and their content have been significantly characterized in the most common candidal species Candida albicans, including the identification of numerous virulence factors and cytoplasmic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 73 publications
5
49
0
Order By: Relevance
“…As reported previously, EVs from C. albicans are round and bilayered particles (Figure 1A) 9 . Similar results were observed for EVs from both C. auris isolates (Figure 1B and 1C), consistent with the reported morphology of other fungal EVs 7,9,12,16,20,23,25,44 . EVs were also analyzed by dynamic light scattering (DLS) to evaluate their global size.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As reported previously, EVs from C. albicans are round and bilayered particles (Figure 1A) 9 . Similar results were observed for EVs from both C. auris isolates (Figure 1B and 1C), consistent with the reported morphology of other fungal EVs 7,9,12,16,20,23,25,44 . EVs were also analyzed by dynamic light scattering (DLS) to evaluate their global size.…”
Section: Resultssupporting
confidence: 90%
“…The literature reports two distinct populations of EVs from other species of Candida, a smaller one ranging usually from 50-70 nm, and a larger group between 100 and 800 nm 9,25, 44 . We found that C. auris releases EVs encompassed by lipid bilayers with size and shape consistent with those from other species.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms underlying the presence and relatively stable attachment of candidal enolase at the cell wall have not yet been identified. Current hypotheses include a sorting role of the 169 amino acid N-terminal domain of this enzyme [25] or the transport of enolase among the cargo of extracellular vesicles [69].…”
Section: Discussionmentioning
confidence: 99%
“…In a downstream analysis by this research group, the extracellular vesicular proteome of these non-albicans Candida spp. was characterized, in which a large portion of identified proteins similarly were classified as moonlighting proteins and understandably featured a large overlap with proteins identified on the cell surface (90). Among the moonlighting proteins identified here, some have immunogenic properties and roles in adhesion to human extracellular matrix proteins (e.g., fibronectin, vitronectin, and laminin).…”
Section: Proteomicsmentioning
confidence: 92%